Ionic liquid‐modified countercurrent chromatographic isolation of high‐purity delphinidin‐3‐rutinoside from eggplant peel. Issue 4 (6th March 2020) - Fan, Chen; Li, Nai; Cao, Xueli; Wen, Lijiao
Abstract: Delphinidin‐3‐rutinoside, a high‐value of anthocyanin, was isolated and purified by ionic liquid (IL)‐modified countercurrent chromatography (CCC) from waste peel of eggplant ( Solanum melongena ), one of the most common vegetables consumed all around the world. Different conventional CCC and IL‐CCC solvent systems were evaluated in respect of partition coefficient ( K ), separation factor ( α ), and stationary phase retention factor ( S f ) to separate polar target and other components. Basic solvent system, kind of ILs, and amount of ILs were systematically optimized by totally K ‐targeted strategy, which drastically reduced the experimental effort. Finally, a novel CCC two‐phase solvent system (methyl tert‐butyl ether–butanol–acetonitrile–1% trifluoroacetic acid water–1‐butyl‐3‐methylimidazolium hexafluorophosphate ([C4 MIM][PF6 ]) [2:4:1:5:0.2; v/v/v/v/v]) was successfully established and applied. The baseline separation of target fraction was obtained in one cycle process. The purity of delphinidin‐3‐rutinoside was over 99%. Moreover, the distribution behavior of different kinds of ILs in biphasic solvent system and the removal method of ILs were explored. The results showed that hydrophobic IL significantly improved the partition of polar anthocyanin in organic solvent system, thereby the separation resolution and stationary phase retention through introducing intermolecular forces. This IL‐modified CCC strategy may be applied for the separation of other anthocyanins from variety of natural food resources and waste.